Помогите, пожалуйста, решить пример)

0 голосов
56 просмотров

Помогите, пожалуйста, решить пример)


image

Алгебра (546 баллов) | 56 просмотров
Дан 1 ответ
0 голосов

     y-3         -(3-y+1-1)        -((4-y)-1)       -((√(4-y) )² -1²)    -(√(4-y)-1)*(√(4-y)+1)
------------ = ----------------- = -------------- = -------------------- = --------------------------=
√(4-y)+1     √(4-y)+1             √(4-y)+1       √(4-y)+1                √(4-y)+1

-(√(4-y)-1) =1-√(4-y)


(86.0k баллов)
0

огромное спасибо!)

0

не за что))